2021
DOI: 10.1155/2021/6086265
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Alleviates Mechanical Allodynia of Rats with Bone Cancer Pain through the Activation of PPAR-γ to Inhibit the NF-κB/NLRP3 Inflammatory Axis in Spinal Cord Neurons

Abstract: Bone cancer pain (BCP) is a serious clinical problem that affects the quality of life of cancer patients. However, the current treatment methods for this condition are still unsatisfactory. This study investigated whether intrathecal injection of rosiglitazone modulates the noxious behaviors associated with BCP, and the possible mechanisms related to this effect were explored. We found that rosiglitazone treatment relieved bone cancer-induced mechanical hyperalgesia in a dose-dependent manner, promoted the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…In the daytime-feeding group, we observed that PG intake at 7 PM led to an increase in PPAR- γ level and a decrease in pNF- κ B and IL-6 levels in liver tissues. Our data support the previous report [ 60 ] that rosiglitazone activated PPAR- γ to inhibit the NF- κ B inflammatory axis.…”
Section: Discussionsupporting
confidence: 93%
“…In the daytime-feeding group, we observed that PG intake at 7 PM led to an increase in PPAR- γ level and a decrease in pNF- κ B and IL-6 levels in liver tissues. Our data support the previous report [ 60 ] that rosiglitazone activated PPAR- γ to inhibit the NF- κ B inflammatory axis.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies suggest that the NF-κB/NLRP3 inflammatory axis performs a crucial part in pain ( Fu et al, 2021b ). Therefore, we decided to elucidate the potential molecular mechanisms by which catalpol inhibit inflammatory pain.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure for extracting proteins was similar to an earlier experiment ( Fu et al, 2021b ). Through i. p. injection of sodium pentobarbital (100 mg/kg), rats were fully sedated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARγ/RXRα has been proven to negatively regulate the NF-κB signal [ 22 ]. As shown in Figure 5 A,B, the protein expression of NF-κB in 95D cells were significantly decreased in DHA-PC, DHA-TG, and DHA-EE groups by 32.8% ( p < 0.01), 21.6% ( p < 0.01), and 15.5% ( p < 0.05) compared to the control group, respectively.…”
Section: Resultsmentioning
confidence: 99%